Halaman Depan Jurnal Sisfokom (Sistem Informasi dan Komputer) Vol. 8 No. 2 2019 - Editor in Chief Sisfokom (ISB Atma Luhur, 2019)
This article contains front-matter of Sisfokom Journal, Volume 8 Number 2 Year 2019, which includes a cover page, title page, editorial team, and table of contents.